International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2535959
|View full text |Cite
|
Sign up to set email alerts
|

All-dielectric prism-grating-prism component realized by direct hydrophilic bonding technology for optical applications in space

Abstract: Here, we report on the approach of realizing an all-fused-silica PGP disperser (prism + grating + prism) by low temperature direct bonding. A surface relief grating with period 660nm and overall depth of approximately 2000nm is sandwiched between two equal prisms. Direct bonding of glass relies on the formation of covalent bonds between hydrophilic silicon-oxide surfaces. Compared to other joining technologies, like adhesive bonding or optical contacting, the established connection is stiff, shows no outgassin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As a preliminary result, we found that small surface roughness correlates with high final bonding strength for all tested uncoated glass substrates 23) and that this parameter is more determinative than the external pressure applied during thermal treatment of the bonded pair. In case of the coated glass substrates, this correlation holds likewise.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…As a preliminary result, we found that small surface roughness correlates with high final bonding strength for all tested uncoated glass substrates 23) and that this parameter is more determinative than the external pressure applied during thermal treatment of the bonded pair. In case of the coated glass substrates, this correlation holds likewise.…”
mentioning
confidence: 63%
“…4,21) This is why PAB becomes increasingly interesting in the field of optics, especially for the manufacturing of high-resolution spectrometers that have to be suitable for space applications. 22,23) Some of the recent design concepts of those high-resolution spectrometers, for example KOESTERS prism based devices, 24) rely on the usage of optical coatings. A KOESTERS prism combines at least two prisms with optical coatings in between to operate as a beam-splitter.…”
mentioning
confidence: 99%
“…To overcome this challenge, it is necessary to affix prisms onto the fused silica grating, forming a GRISM structure that allows the light to exhibit a suitable angle deviation. Numerous studies have verified the feasibility of this strategy, along with several reports of GRISMs [13][14][15][16]. These reports showcase exceptional properties, such as flattened angular dispersion, outstanding spectral resolution, and enhanced system integration.…”
Section: Introductionmentioning
confidence: 84%
“…9a). Bonding on plane surface has been reported for manufacturing of grism [16,17] but should be investigated for subwavelength gratings and adjusted for non-planar substrate. The second approach consists in taking benefit of the flexibility of the nanoimprint stamp to perform a replication on curved gratings before the transfer of the patterns (Fig.…”
Section: Outlook Towards Curved Substratesmentioning
confidence: 99%